Effects of ocean acidification on the interaction between calcifying oysters (Ostrea chilensis) and bioeroding sponges (Cliona sp.) - Böök, Imke M.; Krieger, Erik C.; Phillips, Nicole E.; Michael, Keith P.; Bell, James J.; Dillon, Wayne D. N.; Cornwall, Christopher E. (Frontiers in Marine Science, 2024)
Ocean acidification can negatively affect a broad range of physiological processes in marine shelled molluscs. Marine bioeroding organisms could, in contrast, benefit from ocean acidification due to reduced energetic costs of bioerosion. Ocean acidification could thus exacerbate negative effects (e.g. reduced growth) of ocean acidification and shell borers on oysters. The aim of this study was to assess the impact of ocean acidification on the oyster Ostrea chilensis, the boring sponge Cliona sp., and their host-parasite relationship. We exposed three sets of organisms 1) O. chilensis, 2) Cliona sp., and 3) O. chilensis infested with Cliona sp. to pHT 8.03, 7.83, and 7.63. Reduced pH had no significant effect on calcification, respiration and clearance rate of uninfested O. chilensis. Low pH significantly reduced calcification leading to net dissolution of oyster shells at pHT 7.63 in sponge infested oysters. Net dissolution was likely caused by increased bioerosion by Cliona sp. at pHT 7.63. Additionally, declining pH and sponge infestation had a significant negative antagonistic effect (less negative than predicted additively) on clearance rate. This interaction suggests that sponge infested oysters increase clearance rates to cope with higher energy demand of increased shell repair resulting from higher boring activity of Cliona sp. at low seawater pH. O. chilensis body condition was unaffected by sponge infestation, pH, and the interaction of the two. The reduction in calcification rate suggests sponge infestation and ocean acidification together would exacerbate direct (reduced growth) and indirect (e.g., increased predation) negative effects on oyster health and survival. Our results indicate that ocean acidification by the end of the century could have severe consequences for marine molluscs with boring organisms.